Mindpowered coaching for professionals : unlocking innovation through cognitive mastery - Oh, Alvin; Loh, Jennifer (Routledge, 2026)
"In an era where digital transformation reshapes every industry, the greatest competitive advantage isn't technology-it's the power of the human mind. MindPowered Coaching (MPC) revolutionizes how leaders and organizations approach innovation, revealing the profound connection between mindset and breakthrough thinking. Drawing from extensive research and real-world applications, this book unveils 22 core principles that form the foundation of the MindPowered Coaching framework. Through detailed case studies of successful implementations across global organizations, readers will discover how to cultivate environments where innovation thrives naturally. The book delves deep into the psychology of creative problem-solving, exploring how mindset shifts can trigger organizational transformation. It presents practical strategies for developing cognitive resilience, enhancing collaborative thinking, and building sustainable innovation practices. Each chapter combines theoretical insights with actionable techniques, providing a comprehensive roadmap for implementing MPC within any organizational context. Perfect for CEOs, business leaders, and professionals navigating the digital age, this book provides the tools to transform how your organization approaches innovation. Whether you're leading a digital transformation or seeking to amplify your team's creative potential, MindPowered Coaching offers the blueprint for turning cognitive capabilities into competitive advantages"-- Provided by publisher.
Keywords: Problem solving.; Personal coaching.; Organizational change.; Technological innovations.; elektronické knihy; electronic books